E-CRM MYSAFFANA FOR OPTIMIZING CUSTOMER AND TRANSACTION DATA AT SAFFANA BOUTIQUE - Masytha Siagian, Nurul; Dwi Sena, Maulana; Madonna Yuma, Febby (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Royal Kisaran, 2026)
Abstract: The development of information technology encourages retail businesses to manage customer and transaction data more effectively. However, many small-scale retailers still rely on manual record-keeping, resulting in unintegrated data and limited decision-making support. This study aims to design and implement a web-based Electronic Customer Relationship Management (E-CRM) system called MySaffana for Saffana Gallery Boutique to optimize customer and transaction data management. The research method includes requirement analysis, system design using UML, implementation using PHP and MySQL, and system testing using black box testing. The results show that the MySaffana system is able to manage customer data, products, transactions, and sales reports in an integrated and efficient manner. System testing indicates that all main features function properly and meet user requirements. Therefore, the developed E-CRM system provides an effective and practical solution for strengthening data-driven decision-making in small-scale retail businesses. Keywords: boutique; customer data management; customer profiling; E-CRM. Abstrak: Perkembangan teknologi informasi mendorong usaha ritel untuk mengelola data pelanggan dan transaksi secara lebih efektif. Namun, banyak usaha ritel skala kecil masih melakukan pencatatan secara manual sehingga data tidak terintegrasi dan kurang optimal dalam mendukung keputusan. Penelitian ini bertujuan untuk merancang dan mengimplementasikan sistem Electronic Customer Relationship Management (E-CRM) berbasis web bernama MySaffana pada Butik Saffana Gallery yang dapat mengoptimalkan pengelolaan data pelanggan dan transaksi. Metode penelitian meliputi analisis kebutuhan, perancangan sistem menggunakan UML, implementasi dengan PHP dan MySQL, serta pengujian menggunakan metode black box testing. Hasil penelitian menunjukkan bahwa sistem MySaffana mampu mengelola data pelanggan, produk, transaksi, dan laporan penjualan secara terintegrasi dan efisien. Pengujian sistem membuktikan seluruh fitur berjalan sesuai fungsi dan kebutuhan pengguna. Dengan demikian, sistem E-CRM berbasis web ini dapat menjadi solusi yang efektif dalam mendukung pengelolaan data dan pengambilan keputusan berbasis data bagi usaha ritel skala kecil. Kata kunci: butik; E-CRM; profil pelanggan; pengelolaan data pelanggan.